มโนทัศน์การกีดกันในวาทกรรมความบ้าของมิเชล ฟูโกต์ - คีตา บุณยพานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This thesis attempts to examine the notion of exclusion Michel Foucault’s Folie et Déraison : Histoire de la folie à l’âge classiqueault. It explores this notion through discourses on madness. It also emphasizes Foucault’s critique of Cartesian subject. The latter sets forth the order of reason to determine the distinction between reason and madness, and yet, between normalcy and the pathology.